THE INFLUENCE OF CADMIUM AS ABIOTIC ELICITOR ON THE PRODUCTION OF PHYTOESTROGENS IN HAIRY ROOT CULTURES OF PSORALEA CORYLIFOLIA - RAMESH K. SATDIVE; SUCHITA KAMBLE; SHRADDHA SINGH; SUDHIR SINGH; DEVANAND P. FULZELE (International Journal of Pharma and Bio Sciences, 2014)
Environmental pollution especially with heavy metals poses serious problem on product synthesis of medicinal plants cultivated in the field. Accordingly, the purpose of this study was to assess in vitro effects of cadmium as abiotic elicitor on phytoestrogens production by Psoralea corylifolia hairy roots. Transformed hairy roots were developed by genetic transformation using Agrobacterium rhizogenes. The stable, transformed and fast growth hairy roots demonstrated high growth rate 7.23% dry weight in growth regulators free Murashige and Skoog’s medium enriched with 8 µM of cadmium. Hairy roots were tested with low and high concentrations of cadmium. Correlation of in vitro cadmium exposure and phytoestrogens production showed that low percentage of cadmium and exposure period was stimulated product synthesis, while high levels of cadmium in nutrient medium and more exposure period impaired the product synthesis. Elevated concentrations of cadmium and increased exposure time decreased the hairy roots growth by five-fold compared to devoid of cadmium in the medium. Cadmium concentrations in cells and medium were determined by Atomic Absorption Spectrophotometer. Maximal cadmium concentrations and treatment period harmfully effects on phytoestrogens production. HPLC revealed that hairy roots tested with 8 µM of cadmium in medium produced phytoestrogens daidzein 1.74% dry weight and genistein 0.23% dry weight on day 2. The results showed that the hairy root growth decreased as a concentration of cadmium increased and related to timedependent manner. The present results revealed that abiotic elicitor cadmium at optimum concentrations stimulated the production of phytoestrogenic isoflavones daidzein and genistein in P. corylifolia hairy roots.